2011
DOI: 10.1021/mp2004675
|View full text |Cite
|
Sign up to set email alerts
|

Induced Pluripotent Stem (iPS) Cells Inhibit Apoptosis and Fibrosis in Streptozotocin-Induced Diabetic Rats

Abstract: Recent data suggests that transplanted bone marrow stem cells improve cardiac function in streptozotocin induced diabetic cardiomyopathy (SIDC). However, whether modified embryonic stem (ES) cells, induced pluripotent stem (iPS) cells, or factors released from these cells can inhibit apoptosis and fibrosis remains completely unknown. Therefore, we hypothesized that transplanted ES cells overexpressing pancreatic transcription factor 1 a (Ptf1a), a propancreatic endodermal transcription factor, iPS cells, or th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 46 publications
3
31
0
Order By: Relevance
“…In return, cardiomyocyte apoptosis is not only an important mechanism of cardiac dysfunction and decreased cardiac function, it also increases the intraventricular pressure load. Researchers have confirmed that myocardial cell apoptosis itself is the cause of myocardial fibrosis [2729]. Our data suggest that Yi-qi-huo-xue improved cardiac function and delayed myocardial fibrosis in diabetic rats via the degradation of myocardial interstitial collagen.…”
Section: Discussionsupporting
confidence: 66%
“…In return, cardiomyocyte apoptosis is not only an important mechanism of cardiac dysfunction and decreased cardiac function, it also increases the intraventricular pressure load. Researchers have confirmed that myocardial cell apoptosis itself is the cause of myocardial fibrosis [2729]. Our data suggest that Yi-qi-huo-xue improved cardiac function and delayed myocardial fibrosis in diabetic rats via the degradation of myocardial interstitial collagen.…”
Section: Discussionsupporting
confidence: 66%
“…Recently, iPSCs have been generated from cardiac ventricular specific cell types instead of the commonly used mouse and human fibroblasts. These cells were effective in reducing fibrosis and the infarct zone following MI [47], and in diabetes-induced cardiomyopathy [48], probably through autocrine or paracrine mechanisms that remain to be determined. More recently, it has been reported that transcription factors such as GATA4, HAND2, MEF2C, and TBX5 (GHMT) can reprogram cardiac fibroblasts into functional cardiac-like myocytes in vitro and in vivo.…”
Section: Induced Pluripotent Stem Cells (Ipscs)mentioning
confidence: 97%
“…Induced pluripotent stem cells (iPSCs) may be used to treat a number of diseases, as they possess the potential for self-renewal and multi-differentiation ( 6 ). It has previously been suggested that transplanted iPSCs were able to inhibit vascular apoptosis and fibrosis, thus improving cardiac function in diabetic rats ( 7 ). However, little is known about the mechanisms by which iPSCs, or factors released from these cells, inhibit adverse cardiac remodeling ( 8 ).…”
Section: Introductionmentioning
confidence: 99%